2013
DOI: 10.1371/journal.pone.0070745
|View full text |Cite
|
Sign up to set email alerts
|

Chemoirradiation for Glioblastoma Multiforme: The National Cancer Institute Experience

Abstract: PurposeStandard treatment for glioblastoma (GBM) is surgery followed by radiation (RT) and temozolomide (TMZ). While there is variability in survival based on several established prognostic factors, the prognostic utility of other factors such as tumor size and location are not well established.Experimental DesignThe charts of ninety two patients with GBM treated with RT at the National Cancer Institute (NCI) between 1998 and 2012 were retrospectively reviewed. Most patients received RT with concurrent and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Glioblastoma multiforme (GBM) is the most aggressive type of glioma, with a median survival of 15 months following standard treatment . The current multimodal treatment regimen—including surgical resection, concurrent chemo‐irradiation and adjuvant temozolomide—has yielded significant improvement in the patient survival . However, glioma invasion makes it difficult to be completely removed, resulting in relapse and death in patients with malignant glioma.…”
mentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most aggressive type of glioma, with a median survival of 15 months following standard treatment . The current multimodal treatment regimen—including surgical resection, concurrent chemo‐irradiation and adjuvant temozolomide—has yielded significant improvement in the patient survival . However, glioma invasion makes it difficult to be completely removed, resulting in relapse and death in patients with malignant glioma.…”
mentioning
confidence: 99%
“…Lower KPS has been observed in patients with VSVZ + GBMs 5,9,11,16 , likely due to their more central location and larger size which could impair the function of the central neural tracts and basal nuclei. In addition, their larger volumes and deeper location may also decrease the likelihood of gross total resections 9,16,3133 . Unlike prior efforts 5,6,15,16 , our analysis accounted for these and other molecular predictors and demonstrated that contact with the VSVZ by GBM is an independent, negative prognosticator.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that identification of poor metabolic response could be effectively used as a risk-adaptive approach for utilization of agents like bevacizumab that are effective in recurrent settings (24, 25). Early application might benefit patients prior to having gross radiographic recurrence.…”
Section: Discussionmentioning
confidence: 99%